2002
DOI: 10.1046/j.1365-2788.2002.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Social timing, clock genes and autism: a new hypothesis

Abstract: We suggest that anomalies in clock genes operating as timing genes in high frequency oscillator systems may underlie the timing deficits of autism. We outline how anomalies in methylation-related genes may also be implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 48 publications
3
96
4
3
Order By: Relevance
“…21 In this candidate gene study, we found significant associations in two of the genes studied: per1 and npas2, with two SNPs in each gene reaching conventional levels of statistical significance. In addition, a high proportion of all possible haplotypes in npas2 was also significant.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…21 In this candidate gene study, we found significant associations in two of the genes studied: per1 and npas2, with two SNPs in each gene reaching conventional levels of statistical significance. In addition, a high proportion of all possible haplotypes in npas2 was also significant.…”
Section: Discussionmentioning
confidence: 59%
“…6 The role of per1 in modulating high-frequency oscillators concerned with communicative timing, [69][70][71] together with our findings of association of per1 with autistic disorder, strengthens the notion that temporal deficits are quintessential to autistic disorder. [21][22][23][24][25][26]28,29,39 Purkinje neurons are important for learning appropriate timing 120,121 and their abnormally low number in the cerebella of autistic subjects 115,122 is considered a keystone biological observation implicating cerebellar dysfunction. 123,124 In this context, reports of a per1 interacting protein (PIPS) in rat that co-translocates with per1 into the nucleus 125 and which is further shown to be required for neuronal growth factor-mediated neuronal survival in P12 cells, 126 tentatively suggests a role for per1 in the lack of Purkinje neurons of the cerebellum in autism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations